Obesity trends and determinant factors in Latin America - Juliana Kain; Fernando Vio; Cecilia Albala
Obesity rates have increased markedly in Latin America, especially during the last 10-15 years, becoming a public health problem in most countries. Prevalence of obesity among preschool children remains low, while among schoolchildren it has increased considerably. Prevalence is high in the adult population, especially among women with less schooling. In developed populations, obesity occurs more frequently among the poor; the opposite occurs in less developed societies, where in households undergoing nutritional transition, underweight can coexist with obesity. The most important determinant factors involved in the increasing obesity prevalence are fetal and infant nutritional conditions (stunting), education and socioeconomic conditions, dietary changes (especially increased total energy intake), and physical inactivity. Because chronic diseases are the main causes of death in the Region and obesity is one of the main risk factors for these diseases, policies to improve economic and educational levels with the implementation of health promotion and prevention should be a priority in every country.